PENDAMPINGAN MEMBACA AL-QUR’AN MENGGUNAKAN METODE IQRA PADA ANAK-ANAK DI DESA CIHANJAWAR PURWAKARTA - Rian Mustofa; Ahmad Fajar (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
The background of the holding of mentoring in reading the Qur'an using the Iqra method for children in Cihanjawar Village Purwakarta is the potential that children in Cihanjawar Village have in reading the Qur'an is quite good, it's just that in practice there are still some weaknesses and mistakes of children in reading the Qur'an. So in this case the researcher decided to do mentoring in reading the Qur'an using the Iqra method, with the hope of increasing the ability and proficiency of children in reading the Qur'an. The purpose of this service is; First, to make it easier for children to learn and understand the Qur'an. Second, to improve the ability and proficiency of children in reciting the Hijaiyah letters. Third, familiarize children in reading the Qur'an. The method used in this service uses Asset Based Community Development (ABCD), in which this technique utilizes all the wealth of assets and potentials that exist in the surrounding community. The results of the service using the Iqra Method in mentoring children to read the Qur'an in Cihanjawar Village, Purwakarta are quite good, this is shown from the enthusiasm and enthusiasm of the children when the mentoring takes place. In practice, mentoring is carried out by introducing and explaining the use of the Iqro method to make it easier for children to read the Qur'an.